Generation of a genetically double-attenuated Plasmodium berghei parasite that fully arrests growth during late liver stage development. - Melanie Schmid; Raphael Beyeler; Reto Caldelari; Ruth Rehmann; Volker Heussler; Magali Roques (PLoS ONE)
Malaria caused by Plasmodium parasites remains a large health burden. One approach to combat this disease involves vaccinating individuals with whole sporozoites that have been genetically modified to arrest their development at a specific stage in the liver by targeted gene deletion, resulting in a genetically attenuated parasite (GAP). Through a comprehensive phenotyping screen, we identified the hscb gene, encoding a putative iron-sulfur protein assembly chaperone, as crucial for liver stage development, making it a suitable candidate gene for GAP generation. Parasites lacking Plasmodium berghei HscB (PbHscB) exhibited normal sporozoite production in mosquitoes, but their liver stage development was severely impaired, characterized by slow growth and delayed expression of merozoite surface protein 1 (MSP1). In vivo experiments demonstrated that PbHscB-deficient parasites exhibited a delay in prepatency of 2-4 days, emphasizing the significance of PbHscB for exo-erythrocytic development. Although knockout of PbHscB alone allowed breakthrough infections, it is a potent candidate for a dual gene deletion strategy. PlasMei2, an RNA-binding protein, was previously found to be crucial for the completion of liver stage development. We generated a PbHscB-PbMei2-double attenuated parasite line, serving as a late liver stage-arresting replication-competent (LARC) GAP, providing a solid block of liver-to-blood stage transition.